Litostratigraphic Study of the Jurassic – Cretaceous boundary in Querdaha Sheet - The Syrian Coastal Chain - عبد الله عبد الكريم; البب سامر; حمدو وردينان (Latakia University Journal -Basic Sciences Series, 2022)
This research contains a litostratigraphic study of the upper Jurassic and lower Cretaceous deposits in the Qardaha sheet 1:50000, by conducting fossil analyzes and rock slices of a group of samples (32 samples) have been taken from rocks of different miens, as revealed in the Qardaha map. The detailed study of four sections in the study area showed the existence of new stratigraphic data that were not previously determined,which is mostly followed the upper Jurassic to Aptian lower Cretaceous This study showed that the Fossils of the benthic foraminifera of the upper Jurassic consisted of dolomitic marly limestone intercalated by thin beds of clayey marl at the top and veins of iron oxides, in addition to limy debris of thickness up to 9 m in Khirbat al-Sindiyana and 3 m in Kharayeb Salem. It also showed that the Lower cretaceous rocks rocks consisted of alternations of clayey limestone, dolomitic limy marl and dolomite, with layers of marl and sandstone, with a thickness of 34 m in Khirbat al-Sindiyana, 7 m in Basmalakh, 5 m in Jawbat al-Burghal, 5 m in Kharayeb Salem The study focused on the boundaries of the known stratigraphic gap at the top of the Upper Jurassic and the bottom of the Lower Cretaceous, where fossils of the benthic foraminifera were identified and their temporal distribution was studied at the local and global levels. We found important species that were not previously mentioned in the studied area.